2017
DOI: 10.1017/s0030605316001319
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of challenges to subsistence agriculture, and crop foraging by wildlife and chimpanzees Pan troglodytes verus in unprotected areas in Sierra Leone

Abstract: The Sierra Leone National Chimpanzee Census Project (SLNCCP) estimated a population of 5,580 individuals distributed across the country with >50% occurring outside protected areas. This census also highlighted the significance of human-chimpanzee competition for resources in areas dominated by farming activities where wild chimpanzees forage on crops. For the purpose of this study, we selected four study areas in two districts in Sierra Leone with high chimpanzee density in agricultural dominated habitats far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…and sorghum ( Sorghum bicolor ) using slash-and-burn intercropping practices. Previous investigations in the study area confirmed the presence of chimpanzees through semi-structured interviews as well as direct observations [23,46].…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…and sorghum ( Sorghum bicolor ) using slash-and-burn intercropping practices. Previous investigations in the study area confirmed the presence of chimpanzees through semi-structured interviews as well as direct observations [23,46].…”
Section: Methodssupporting
confidence: 67%
“…In our model, settlements and human presence did not influence chimpanzees’ relative abundance, possibly due to human tolerance for chimpanzees [46] and low levels of hunting in our study area [7]. Therefore, at a spatial level, human presence did not impact chimpanzee presence.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These five faunal groups happened to be the ones most consumed before the EVD epidemic and are hence potentially preferred. It is also worthy to note that, among these faunal groups, monkeys, rodents and hogs are also well known for their crop-foraging habits (Garriga et al, 2018), which may have additionally influenced their continued hunting, consumption and commercialization in the region (Duonamou et al, in press). Although LeBreton et al (2006) found that disease risk perception in Cameroon was only significant for wildmeat butchering rather than its consumption, our findings suggest that when it comes to EVD, the belief that a species could act as a carrier or a vector of EVD could also significantly influence people's consumption behavior.…”
Section: Discussionmentioning
confidence: 99%